Preparation method of concrete crystal nucleus early strength agent

The microsphere structure is formed through ultrasonic dispersion and atomization nozzle technology, and hollow porous microspheres are reacted at high temperatures, which solves the problems of agglomeration of early strength agents in the prior art and reduces the compressive strength, and achieves good dispersion and early strength improvement.

CN119551925APending Publication Date: 2025-03-04SHANDONG SHITONG HIGHWAY CONSTR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411760368.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing concrete crystal core premature strength agents require dispersants and surfactants to avoid agglomeration during production and use, but these additives will cause an increase in the concrete gas content, thereby reducing the compressive strength.

Method used

The nano-calcium silicate and sodium alginate aqueous solution were dispersed by ultrasonic to form an emulsion, and then the soluble calcium salt solution was dripped into the atomization nozzle to form a microsphere structure, and reacted at high temperature to form a hollow porous microsphere structure, avoiding the use of additional dispersants.

Benefits of technology

The good dispersion and early strength improvement of crystalline core early strength agent are achieved, while reducing the introduction of gas in concrete and avoiding the reduction of compressive strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167484830000061
    Figure BDA0005167484830000061
  • Figure BDA0005167484830000071
    Figure BDA0005167484830000071
Patent Text Reader

Abstract

The invention discloses a preparation method of a concrete crystal nucleus early strength agent. The preparation method of the concrete crystal nucleus early strength agent comprises the following steps: adding nano calcium silicate into a sodium alginate aqueous solution, carrying out ultrasonic dispersion to form an emulsion, dropwise adding the emulsion into an excessive soluble calcium salt solution through an atomizing nozzle to form a microsphere emulsion, filtering and centrifugally separating the microsphere emulsion to obtain calcium alginate-calcium silicate microspheres, and drying the calcium alginate-calcium silicate microspheres to obtain the concrete crystal nucleus early strength agent. Then pouring the microspheres into dihydrate gypsum micro powder to be fully mixed to form nano calcium silicate-gypsum microspheres, and finally blowing the nano calcium silicate-gypsum microspheres into a high-temperature furnace kiln through an air blower to react to obtain the powder concrete crystal nucleus early strength agent. The preparation method provided by the invention not only realizes resource utilization of industrial solid waste gypsum, but also realizes good dispersity of the calcium silicate crystal nucleus early strength agent in a powder state, avoids agglomeration of the crystal nucleus early strength agent, improves the early strength effect of the crystal nucleus early strength agent, and reduces the adverse effect on the performance of the existing product due to the use of a surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to a concrete nucleus early strength agent and a preparation method thereof. Background Art

[0002] Nucleus early strength agent is a new type of early strength agent used in concrete. It mainly reduces the nucleation barrier of calcium silicate hydrate by inducing calcium silicate nuclei, thereby improving its early strength. At present, in the production and use of nucleus early strength agent, in order to avoid nucleus agglomeration, dispersants and surfactants are generally required to disperse the generated nucleus early strength agent. The dispersibility of the dispersant is used to avoid the agglomeration of the nucleus early strength agent. Therefore, it is often necessary to prepare it into a suspension to achieve its stable dispersion, and then it can be evenly dispersed in concrete to achieve the early strength effect of the nucleus. There are few products based on powdered nucleus early strength agent. However, since the surfactant / dispersant that prevents the agglomeration of the nucleus early strength agent often has a certain air entraining property, it often leads to an increase in the air content of the concrete. Generally, the air content increases by 1%, and its compressive strength decreases by 5%. Therefore, reducing or avoiding the use of surfactants / dispersants can reduce the introduction of gas into the concrete and further improve the early strength of the nucleus early strength agent. Summary of the invention

[0003] Based on the problems existing in the above-mentioned background technology, the present invention provides a method for preparing a concrete nucleus early strength agent, which does not require the additional use of a dispersant and is prepared into a powder material through structural optimization. It can avoid the agglomeration of the nucleus early strength agent and achieve a good early strength effect.

[0004] A method for preparing a concrete nucleus early strength agent comprises the following steps:

[0005] (1) adding nano-calcium silicate to a sodium alginate aqueous solution and dispersing the solution through ultrasonication to form an emulsion, wherein the nano-calcium silicate and the sodium alginate aqueous solution are uniformly mixed through ultrasonic dispersion;

[0006] The mass fractions of the raw material components in step (1) include the following:

[0007] 5-8 parts of nano calcium silicate,

[0008] 100 parts of sodium alginate aqueous solution,

[0009] The mass concentration of the sodium alginate aqueous solution is 1-2%;

[0010] The particle size of the nano calcium silicate is not greater than 100 nm;

[0011] The ultrasonic dispersion time is 5 to 10 minutes;

[0012] (2) dripping the emulsion obtained in step (1) into an excess soluble calcium salt solution through an atomizing nozzle to form a microsphere emulsion;

[0013] The diameter of the atomizing nozzle in step (2) is 10 to 50 μm;

[0014] The mass concentration of the soluble calcium salt solution is 5-16%, and the soluble calcium salt is calcium nitrate or calcium chloride. The excessive soluble calcium salt solution used means that after all the emulsion is dropped into the soluble calcium salt solution and the reaction is complete, the soluble calcium salt solution still contains a certain concentration of calcium ions;

[0015] The purpose of this step is to transform the calcium silicate emulsion from sodium alginate to calcium alginate to form a microsphere structure with calcium alginate gel wrapped outside and calcium silicate suspension filled inside;

[0016] (3) filtering and centrifuging the microsphere emulsion formed in step (2) to obtain calcium alginate-calcium silicate microspheres;

[0017] (4) pouring the calcium alginate-calcium silicate microspheres obtained in step (3) into the dihydrate gypsum powder and mixing them thoroughly, placing them on a sieve, and vibrating and screening them until there is no residue on the sieve, repeating this process three times until the mass of the microspheres after screening no longer increases and the surface of the microspheres is fully contaminated with a layer of dihydrate gypsum, thereby forming nano calcium silicate-gypsum microspheres;

[0018] This step is to use the permeability and wettability of calcium alginate microspheres to make a layer of dihydrate gypsum adhere to their surface;

[0019] (5) blowing the nano calcium silicate-gypsum microspheres obtained in step (4) into a high-temperature kiln through a blower, and reacting in the high-temperature kiln for 3 to 5 minutes, opening the fine mesh at the upper opening of the high-temperature kiln, blowing the microspheres out through the upper opening, and naturally cooling and precipitating to obtain the powder concrete nucleus early strength agent of the present invention;

[0020] The temperature in the high temperature furnace in step (5) is 1280-1350°C;

[0021] The high-temperature kiln described in step (5) is a sulfur dioxide environment, with an upper opening and a lower opening. The microspheres are blown into the kiln through a blower at the lower opening, and sulfur dioxide gas is continuously passed through to ensure that the microspheres float in the air and are dispersed with each other; the upper opening is a fine mesh with an aperture of no more than 0.01 mm, ensuring that sulfur dioxide gas is discharged while the microspheres cannot pass through. Sulfur dioxide can be recycled under sealed conditions, does not pollute the environment, and realizes the resource utilization of harmful sulfur dioxide gas.

[0022] In step (5), the microspheres are blown into a blast furnace kiln at a temperature of 1280 to 1350° C., mainly to ensure that the calcium sulfate contaminated on the surface of the microspheres in step (4) melts, thereby forming a microsphere structure. At the same time, in order to avoid excessive decomposition of calcium sulfate, the high-temperature furnace kiln is required to be an environment full of sulfur dioxide, which promotes its formation of a molten state while reducing its decomposition rate. At the same time, under this temperature condition, the water contained in the calcium alginate evaporates rapidly, and the calcium alginate also undergoes a pyrolysis reaction to generate calcium oxide, which is bonded to the molten calcium sulfate to form a microsphere as a whole. The gas generated by the evaporation of water and the pyrolysis reaction causes the molten calcium sulfate microsphere to expand, and under the action of the gas, a porous microsphere structure is formed with nano-calcium silicate particles but a hollow structure and calcium sulfate and a small amount of calcium oxide as a coating layer on the surface. Controlling the time within 3 to 5 minutes can ensure that the calcium sulfate forms a microsphere under the action of surface tension after forming a molten state, and avoid the long-term high temperature condition causing the calcium sulfate to decompose and generate excessive calcium oxide and sulfur dioxide.

[0023] The concentration of the soluble calcium salt solution is maintained at a certain relatively high concentration, so that the calcium alginate content is increased, and excessive calcium oxide is formed during pyrolysis and mixed with calcium sulfate to form an outer microsphere structure. When used in concrete, the calcium oxide easily absorbs water and expands, causing the structure to disintegrate rapidly, thereby promoting the precipitation of internal calcium silicate crystal nuclei.

[0024] Furthermore, the dihydrate gypsum of the present invention is an industrial solid waste with a content of 93% to 95% of calcium sulfate dihydrate, a particle size of no more than 20 μm, partial decomposition at above 1200°C, melting at above 1280°C, and simultaneous decomposition, but incomplete decomposition. In a sulfur dioxide environment, its decomposition slows down. Reaction in a sulfur dioxide gas environment at 1280 to 1350°C for 3 to 5 minutes can form a microsphere structure on the surface, which is hollow inside and contains nano calcium silicate.

[0025] A concrete crystal nucleus early strength agent prepared by the preparation method has a hollow porous microsphere structure, a surface coating layer of calcium sulfate and calcium oxide, and nano calcium silicate particles inside.

[0026] The method for using the concrete crystal nucleus early strength agent of the present invention comprises: after the concrete crystal nucleus early strength agent is evenly mixed with cement and sand aggregate, water and admixture are added, and the crystal nucleus early strength agent, water and admixture shall not be mixed in advance. Because after it meets water, the calcium sulfate in the surface micro-shell will dissolve, and the calcium oxide will easily expand due to water absorption, resulting in the destruction of the microsphere structure, so that the calcium silicate crystal nuclei in different microspheres are easy to agglomerate in water, affecting their dispersibility. The dosage of the concrete crystal nucleus early strength agent is 1% to 5% of the cement dosage.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The preparation method of the crystal nucleus early strength agent of the present invention realizes the resource utilization of industrial solid waste gypsum, realizes the good dispersibility of the calcium silicate crystal nucleus early strength agent in the powder state, improves the early strength effect of the crystal nucleus early strength agent, and reduces the adverse effects of the use of surfactants on the performance of existing products.

[0029] (2) The present invention adopts microspheres with calcium sulfate as the main component and calcium oxide as the auxiliary component, which can not only increase the fluidity of concrete, but also avoid the agglomeration of calcium silicate crystal nuclei, thereby ensuring its dispersibility and good dispersion uniformity in concrete, and ensuring the performance of its crystal nucleus effect; at the same time, calcium sulfate itself has early strength, calcium oxide has a micro-expansion effect, and the crystal nucleus calcium silicate has the effect of aggravating the early shrinkage of concrete. The mutual coordination makes the expansion and contraction offset each other, maintains the volume stability of concrete, and reduces the adverse effect of early shrinkage on the volume stability of concrete. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific examples. It should be noted that the following examples are only further descriptions of the present invention and cannot be understood as limiting the scope of protection of the present invention.

[0031] Example 1

[0032] The specific preparation steps of a concrete nucleus early strength agent are as follows:

[0033] (1) adding 8 parts of nano calcium silicate with a particle size of 100 nm to 100 parts of a 1% sodium alginate aqueous solution to form an emulsion by ultrasonic dispersion;

[0034] (2) spraying the emulsion into a 5% calcium nitrate solution through an atomizing nozzle with a diameter of 50 μm to form a microsphere emulsion;

[0035] (3) filtering and centrifuging the microsphere emulsion formed in (2) to obtain microspheres;

[0036] (4) pouring the microspheres obtained in step (3) into the dihydrate gypsum powder and mixing them thoroughly, placing them on a sieve, and vibrating and screening them until there is no residue on the sieve, repeating this process three times until the mass of the microspheres after screening no longer increases, ensuring that the surface of the microspheres is fully contaminated with a layer of dihydrate gypsum to form nano calcium silicate-gypsum microspheres;

[0037] (5) blowing the nano calcium silicate-gypsum microspheres obtained in step (4) into a high-temperature kiln at a temperature of 1280° C. through a blower, reacting the microspheres in the kiln for 5 minutes, opening the fine mesh of the upwind port, blowing the microspheres out through the upwind port, and cooling and precipitating them naturally to obtain a powder crystal nucleus early strength agent;

[0038] The desulfurized gypsum is phosphogypsum with a calcium sulfate dihydrate content of 95% and an average particle size of 20 μm;

[0039] The upper opening of the high temperature furnace is a fine mesh with an aperture of 10 μm.

[0040] Example 2

[0041] The specific preparation steps of a concrete nucleus early strength agent are as follows:

[0042] (1) adding 5 parts of nano calcium silicate with a particle size of 80 nm to 100 parts of a 2% sodium alginate aqueous solution to form an emulsion by ultrasonic dispersion;

[0043] (2) spraying the emulsion into a 16% calcium chloride solution through an atomizing nozzle having a diameter of 10 μm to form a microsphere emulsion;

[0044] (3) filtering and centrifuging the microsphere emulsion formed in (2) to obtain microspheres;

[0045] (4) pouring the microspheres obtained in step (3) into the dihydrate gypsum powder and mixing them thoroughly, placing them on a sieve, and vibrating and screening them until there is no residue on the sieve, repeating this process three times until the mass of the microspheres after screening no longer increases, ensuring that the surface of the microspheres is fully contaminated with a layer of dihydrate gypsum to form nano calcium silicate-gypsum microspheres;

[0046] (5) blowing the nano calcium silicate-gypsum microspheres obtained in step (4) into a high-temperature kiln at a temperature of 1350° C. through a blower, reacting the microspheres in the kiln for 3 minutes, opening the fine mesh of the upwind port, blowing the microspheres out through the upwind port, and cooling and precipitating naturally to obtain a powder crystal nucleus early strength agent;

[0047] The dihydrate gypsum is desulfurized gypsum with a dihydrate calcium sulfate content of 93% and an average particle size of 8 μm;

[0048] The upper opening of the high temperature furnace is a fine mesh with a pore size of 1 μm.

[0049] Example 3

[0050] The specific preparation steps of a concrete nucleus early strength agent are as follows:

[0051] (1) adding 6 parts of nano calcium silicate with a particle size of 60 nm to 100 parts of a 1.2% sodium alginate aqueous solution to form an emulsion by ultrasonic dispersion;

[0052] (2) spraying the emulsion into a 10% calcium nitrate solution through an atomizing nozzle with a diameter of 15 μm to form a microsphere emulsion;

[0053] (3) filtering and centrifuging the microsphere emulsion formed in (2) to obtain microspheres;

[0054] (4) pouring the microspheres obtained in step (3) into the dihydrate gypsum powder and mixing them thoroughly, placing them on a sieve, and vibrating and screening them until there is no residue on the sieve, repeating this process three times until the mass of the microspheres after screening no longer increases, ensuring that the surface of the microspheres is fully contaminated with a layer of dihydrate gypsum to form nano calcium silicate-gypsum microspheres;

[0055] (5) blowing the nano calcium silicate-gypsum microspheres obtained in step (4) into a high-temperature kiln at a temperature of 1300° C. through a blower, reacting the microspheres in the kiln for 4 minutes, opening the fine mesh of the upwind port, blowing the microspheres out through the upwind port, and naturally cooling and precipitating to obtain a powder crystal nucleus early strength agent;

[0056] The desulfurized gypsum is a desulfurized gypsum with a calcium sulfate dihydrate content of 94% and an average particle size of 6 μm;

[0057] The upper opening of the high temperature furnace is a fine mesh with an aperture of 2 μm.

[0058] Comparative Example 1

[0059] The difference from Example 3 is that the particle size of calcium silicate is 240 nm.

[0060] Comparative Example 2

[0061] The difference from Example 3 is that the concentration of the sodium alginate solution is 0.5%.

[0062] Comparative Example 3

[0063] The difference from Example 3 is that the concentration of the sodium alginate solution is 2.5%.

[0064] The concentration of sodium alginate solution was higher than 2%, which resulted in the solution being too viscous and calcium silicate being difficult to disperse evenly, so no further preparation was performed.

[0065] Comparative Example 4

[0066] The difference from Example 3 is that the diameter of the atomizing nozzle is 5 μm.

[0067] Comparative Example 5

[0068] The difference from Example 3 is that the diameter of the atomizing nozzle is 100 μm.

[0069] Comparative Example 6

[0070] The difference from Example 3 is that the concentration of the calcium nitrate solution is 2%.

[0071] Comparative Example 7

[0072] The difference from Example 3 is that the concentration of the calcium nitrate solution is 20%.

[0073] Comparative Example 8

[0074] The difference from Example 3 is that the temperature in the high-temperature furnace is 1200°C.

[0075] Comparative Example 9

[0076] The difference from Example 3 is that the temperature inside the high-temperature furnace is 1400°C.

[0077] Comparative Example 10

[0078] The difference from Example 3 is that the reaction time in the high-temperature furnace is 2 minutes.

[0079] Comparative Example 11

[0080] The difference from Example 3 is that the reaction time in the high-temperature furnace is 6 minutes.

[0081] The crystal nucleus early strength agent prepared in the above embodiment and comparative example was tested for early strength performance according to the provisions of GB 8076. The dosage of the crystal nucleus early strength agent was the dosage recommended by the manufacturer, and the dosage of the crystal nucleus early strength agent of the present invention was 2% of the cement dosage. The commercially available crystal nucleus early strength agent 1 was Devino Set Control Tech ES-A / B early strength activator, the commercially available crystal nucleus early strength agent 2 was Xinyi synthetic seed early strength agent S7045, and the commercially available crystal nucleus early strength agent 3 was Shanghai Sanrui VIVID-300 (MCN) crystal nucleus early strength agent. When preparing concrete according to GB 8076, the early strength agent should be mixed evenly with cement and sand and gravel aggregate, and then water and admixtures should be added. The results are shown in Table 1.

[0082] Table 1 Performance indexes of crystal nucleus early strength agent

[0083]

[0084]

[0085] From the data in Table 1, we can find that:

[0086] Comparison of Example 3 and three commercially available crystal nucleus early strength agents shows that the 12h compressive strength, 1d compressive strength, 3d compressive strength and 28d volume stability ratio of the crystal nucleus are significantly improved by the modification preparation of the present invention. This shows that the present invention has obvious technical advantages and application effects compared with the existing products.

[0087] Comparison of Example 3 with Comparative Example 1 shows that the compressive strength ratio of the comparative example at different ages is significantly reduced, and the 28d shrinkage rate is slightly increased. This is because the particle size of the nano calcium silicate used is too large, which not only reduces its own crystal nucleation effect, but also makes it easy to bond with the molten calcium sulfate during the roasting process under high temperature conditions, affecting its crystal nucleation effect. Therefore, it is necessary to control the particle size of the crystal nucleus not to be too large.

[0088] Comparison of Example 3 and Comparative Example 2 shows that the compressive strength ratio of the comparative example at different ages is lower. This is mainly because the concentration of the sodium alginate solution is too low, and the formed calcium alginate gel microsphere wrapping layer is relatively thin, which is easy to explode rapidly under the action of internal water vapor directly under high temperature conditions, causing the contaminated calcium sulfate to be scattered into the air and blown out without forming microspheres, resulting in poor dispersion of the crystal nucleus, affecting the early strength effect of the crystal nucleus, and increasing its shrinkage rate.

[0089] Comparison of Example 3 with Comparative Example 4 and Comparative Example 5 shows that the compressive strength ratio of Comparative Example 4 and Comparative Example 5 at different ages is reduced. Comparative Example 4 is because the atomized particle size is too small, and the microspheres formed in the later stage are too small, resulting in a small spacing between the hollow structure formed between the crystal nucleus and the calcium sulfate, which is easy to adhere to the calcium sulfate microspheres, affecting the crystal nucleus effect. Comparative Example 5 is because the atomized particle size is too large, and the microspheres formed in the later stage are too large, resulting in excessive calcium oxide formed by the pyrolysis of calcium alginate, which is mixed with the crystal nucleus, resulting in an increase in crystal nucleus impurities, and too many crystal nucleus particles, which are easy to deteriorate at high temperature and easily agglomerate, resulting in a decrease in its crystal nucleus effect.

[0090] Comparison of Example 3 with Comparative Example 6 and Comparative Example 7 shows that the compressive strength ratio of Comparative Example 6 and Comparative Example 7 at different ages is reduced. The calcium nitrate concentration in Comparative Example 6 is too low, resulting in poor mechanical properties of the calcium alginate microspheres formed, which are easy to break. They are broken during mixing with calcium sulfate and later heating, resulting in the mixing of internal calcium silicate and external calcium sulfate, the destruction of the structure, and the degradation of performance. The concentration of calcium nitrate solution is maintained at a certain higher concentration, so that the calcium alginate content increases, and excessive calcium oxide is formed during pyrolysis to mix with calcium sulfate to form an outer microsphere structure. When used in concrete, calcium oxide easily absorbs water and expands, causing the structure to disintegrate rapidly and promoting the precipitation of internal calcium silicate nuclei. However, when the calcium nitrate concentration is too high, the calcium alginate content in the calcium alginate microspheres is too high, and too much calcium oxide is generated by pyrolysis, which causes the surface structure of the microspheres to be unstable, affecting the dispersibility of the nuclei, and instead causing the early strength performance to decline.

[0091] Comparison of Example 3 with Comparative Examples 8 and 9 shows that the compressive strength ratios of Comparative Examples 6 and 7 at different ages are reduced. When the kiln temperature in Comparative Example 6 is 1200°C, less calcium sulfate melts, the microspheres formed have poor structure, and even fail to form microspheres. A large number of calcium silicate crystal nuclei in the product leak out of the microspheres and agglomerate. When the kiln temperature in Comparative Example 7 is 1400°C, the kiln temperature is too high, and the molten calcium sulfate is easily decomposed to produce a large amount of gas, forming a large amount of calcium oxide powder precipitation, which makes the structural stability worse and even fails to form microspheres. A large number of calcium silicate crystal nuclei leak out of the microspheres, which are easy to agglomerate, the dispersibility is poor, and the early strength performance is reduced.

[0092] Comparison of Example 3 with Comparative Examples 10 and 11 shows that the compressive strength ratios of Comparative Examples 10 and 11 at different ages are lower. In Comparative Example 10, the reaction time in the kiln is too short, resulting in insufficient melting of calcium sulfate, unstable microsphere structure, and a large amount of calcium silicate crystal nuclei leaking out of the product, resulting in agglomeration. In Comparative Example 11, the reaction time in the kiln is too long, and the molten state of calcium sulfate is easily decomposed to produce a large amount of sulfur dioxide gas, forming a large amount of calcium oxide powder precipitation, which makes the structural stability worse or even unable to form microspheres, a large amount of calcium silicate crystal nuclei leaking out of the microspheres, the dispersibility worsens, and the early strength performance decreases.

Claims

1. A method for preparing a concrete nucleus early strength agent, characterized in that: The steps include: (1) adding nano calcium silicate into a sodium alginate aqueous solution and dispersing the mixture through ultrasonication to form an emulsion; The particle size of the nano calcium silicate is not greater than 100 nm; (2) dripping the emulsion obtained in step (1) into an excess soluble calcium salt solution through an atomizing nozzle to form a microsphere emulsion; The mass concentration of the soluble calcium salt solution is 5 to 16%; (3) filtering and centrifuging the microsphere emulsion formed in step (2) to obtain calcium alginate-calcium silicate microspheres; (4) pouring the calcium alginate-calcium silicate microspheres obtained in step (3) into the dihydrate gypsum powder and mixing them thoroughly, placing them on a sieve, and vibrating and screening them until there is no residue on the sieve, repeating this process three times until the mass of the microspheres after screening no longer increases and the surface of the microspheres is fully contaminated with a layer of dihydrate gypsum, thereby forming nano calcium silicate-gypsum microspheres; (5) Blowing the nano calcium silicate-gypsum microspheres obtained in step (4) into a high-temperature kiln through a blower, and reacting in the high-temperature kiln for 3 to 5 minutes, opening the fine mesh at the upper opening of the high-temperature kiln, blowing the microspheres out through the upper opening, and naturally cooling and precipitating to obtain the powder concrete crystal nucleus early strength agent.

2. The preparation method according to claim 1, characterized in that: The mass fractions of the raw material components in step (1) include the following: 5-8 parts of nano calcium silicate, 100 parts of sodium alginate aqueous solution, The mass concentration of the sodium alginate aqueous solution is 1-2%.

3. The preparation method according to claim 1, characterized in that: The ultrasonic dispersion time in step (1) is 5 to 10 minutes.

4. The preparation method according to claim 1, characterized in that: The diameter of the atomizing nozzle in step (2) is 10 to 50 μm.

5. The preparation method according to claim 1, characterized in that: The soluble calcium salt in step (2) is calcium nitrate or calcium chloride.

6. The preparation method according to claim 1, characterized in that: The temperature in the high-temperature furnace in step (5) is 1280-1350°C.

7. The preparation method according to claim 6, characterized in that: The high-temperature furnace in step (5) is a sulfur dioxide environment, with an upper opening and a lower opening. The microspheres are blown into the furnace through a blower at the lower opening and continuously pass through sulfur dioxide gas. The upper opening is a fine mesh with an aperture of no more than 0.01 mm.

8. The preparation method according to claim 1, characterized in that: The dihydrate gypsum described in step (4) is industrial solid waste with a calcium sulfate dihydrate content of 93% to 95% and a particle size of no more than 20 μm.

9. A concrete nucleus early strength agent obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The concrete crystal nucleus early strength agent is a hollow porous microsphere structure, with a surface coating of calcium sulfate and calcium oxide and nano calcium silicate particles inside.

10. A method for using the concrete nucleus early strength agent obtained by the preparation method according to any one of claims 1 to 8, characterized in that: include: After the concrete crystal nucleus early strength agent is uniformly mixed with cement and sand and gravel aggregate, water and admixture are added. The dosage of the concrete crystal nucleus early strength agent is 1% to 5% of the cement dosage.